(untitled) (Práxis Educativa, 2020)
The presidential elections held in Uruguay in October and November 2019 defined the end of a period of three successive governments of the center-left party Frente Amplio and the arrival in government of a right-wing coalition led by the Partido Nacional. In education, the development of a conservative perspective, which is at the base of the educational proposals of the new government, began to develop in the height of the boom of the previous governments. The present article intends to analyze how this process of generating a conservative vision of education was taking shape in the last ten years through the presentation of the so-called “privately managed public education” as an alternative to public education. The theoretical perspective that informs the whole work is located from the logic of the political analysis of the discourse and the methodological approach is made from the consideration of documentary sources. Keywords: Education. Conservatism. Uruguay.